2014
DOI: 10.1126/science.1248636
|View full text |Cite
|
Sign up to set email alerts
|

Toddler: An Embryonic Signal That Promotes Cell Movement via Apelin Receptors

Abstract: It has been assumed that most, if not all, signals regulating early development have been identified. Contrary to this expectation, we identified 28 candidate signaling proteins expressed during zebrafish embryogenesis, including Toddler, a short, conserved, and secreted peptide. Both absence and overproduction of Toddler reduce the movement of mesendodermal cells during zebrafish gastrulation. Local and ubiquitous production of Toddler promote cell movement, suggesting that Toddler is neither an attractant no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
644
3
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 530 publications
(676 citation statements)
references
References 66 publications
(127 reference statements)
21
644
3
8
Order By: Relevance
“…Apela Binds to APJ with High Affinity-Apela induces the internalization of APJ in transfected cell lines overexpressing APJ (13,14). However, binding kinetics between apela and APJ has not been demonstrated.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Apela Binds to APJ with High Affinity-Apela induces the internalization of APJ in transfected cell lines overexpressing APJ (13,14). However, binding kinetics between apela and APJ has not been demonstrated.…”
Section: Resultsmentioning
confidence: 99%
“…Because the APJ-null zebrafish shares the same phenotype as apela mutants during embryogenesis, apela was identified as the cognate peptide ligand for the APJ receptor (13,14). In addition, apela binds to APJ and induces the internalization of APJ in receptor-transfected cell lines (13,14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The Apela transcript had been annotated as a lncRNA in zebrafish (ENSDARG00000094729), mouse (Gm10664), and human (LOC100506013), but was also found to be a peptide-coding mRNA in zebrafish (Chng et al, 2013;Pauli et al, 2014). Apela consists of 54 amino acids that include a signal peptide sequence and is highly conserved among vertebrates.…”
Section: (3) Apelamentioning
confidence: 99%
“…Although lncRNAs do not harbor apparent open reading frames (ORFs) for proteins of >100 amino acids, recent studies have identified a subset of lncRNAs that actually encode polypeptides of <100 amino acids (Fig. 1A) (Anderson et al, 2015;Kondo et al, 2010;Matsumoto et al, 2017;Nelson et al, 2016;Pauli et al, 2014).…”
Section: Introductionmentioning
confidence: 99%